Long‐term safety of a weekly and monthly subcutaneous buprenorphine depot (CAM2038) in the treatment of adult out‐patients with opioid use disorder. (3rd June 2019) - Frost, Michael; Bailey, Genie L.; Lintzeris, Nicholas; Strang, John; Dunlop, Adrian; Nunes, Edward V.; Jansen, Jakob Billeskov; Frey, Lars Chemnitz; Weber, Bernd; Haber, Paul; Oosman, Sonia; Kim, Sonnie; et al.
Abstract: Aims: To assess the long‐term safety of subcutaneous buprenorphine (CAM2038) weekly and monthly depots. Design: Phase 3, open‐label, observational, multi‐centre 48‐week trial (ClinicalTrials.gov NCT02672111). Setting: Twenty‐six out‐patient sites (United States, United Kingdom, Hungary, Denmark, Sweden, Germany, Australia) between 14 December 2015 and 12 April 2017. Participants: Two hundred and twenty‐eight adults with opioid use disorder; 227 received CAM2038 (37 initiated onto CAM2038 and 190 converted from sublingual buprenorphine). Interventions: CAM2038 weekly (8, 16, 24 or 32 mg) or monthly (64, 96, 128 or 160 mg) with flexible dosing and individualized titration utilizing multiple CAM2038 weekly and monthly doses. Measurements: Safety variables, urine toxicology samples and self‐reported illicit opioid use were collected at each visit. Participants were administered a patient satisfaction survey at months 6 and 12, completed by 162 of 227 (71.4%) participants. Findings: The study treatment period was completed by 167 of 227 (73.6%) participants. At least one treatment‐emergent adverse event (TEAE) was reported by 143 of 227 (63.0%) participants, of whom 60 of 227 (26.4%) reported as being drug‐related. Most of the TEAEs, reported by 128 of 227 (56.4%) of participants, were mild or moderate in intensity. Injection‐site reactions were reported by 46 of 227 (20.3%) participants, with most [45 of 46 (97.8%)] reported as mild to moderate. Five participants (2.2%) discontinued the study drug due to a TEAE, two cases (0.9%) of which were injection‐site‐related. No serious adverse events were attributed to the study drug. Among those remaining in the study, the percentage of opioid‐negative urine tests combined with self‐reports was 63.0% (17 of 27) in new‐to‐treatment participants and 82.8% (111 of 134) for those converted from sublingual buprenorphine. Participants reported high levels of satisfaction with CAM2038. Conclusions: Subcutaneous buprenorphine delivered weekly or monthly (CAM2038) was well tolerated, with a systemic safety profile consistent with the known profile of sublingual buprenorphine. CAM2038 weekly and monthly was associated with high retention rates and low levels of illicit opioid use throughout this study.